Does sales growth, asset structure, company size and cash flow stability affect stock prices? - Nugraha, Nugi Mohammad; Fitria, Bulan Tati; Nurlaela, Reni; Nugraha, Deden Novan Setiawan; Torong, Riska Br (Management and Entrepreneurship: Trends of Development, 2021)
This research aims to determine the effect of sales growth variables, asset structure, company size and cash flow stability against stock prices in manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. Sales growth variable is measured using sales, asset structure variable is measured using total assets, company size variable is measured using the natural logarithm of total assets and cash flow stability is measured using net income. This research uses secondary data, in the form of financial reports and other related information from the financial industry listed on the Indonesia Stock Exchange for the period 2014-2018. The selection of this study was related to 75 companies in the manufacturing sector, with a sample of 42 companies using purposive sampling method. The data analysis method used is panel data regression analysis (common effect) with a significant level of 0.05. Based on the results the research conducted shows that, partially the sales growth variable has no effect on stock prices, the asset structure variable has no effect on stock prices, the firm size variable has a significant effect on stock prices and the cash flow stability variable has no effect on stock prices.JEL Classification: G12, G32, L11.